2009
DOI: 10.1111/j.1442-9071.2009.02093.x
|View full text |Cite
|
Sign up to set email alerts
|

Graves' ophthalmopathy and gene polymorphisms in interleukin‐1α, interleukin‐1β, interleukin‐1 receptor and interleukin‐1 receptor antagonist

Abstract: This is the first study to show a positive correlation between polymorphisms in the IL-1alpha and IL-1RA genes and susceptibility to GO. These findings promote further research into genetic correlates of GO.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(32 citation statements)
references
References 54 publications
(105 reference statements)
1
29
2
Order By: Relevance
“…Several studies have reported conflicting results regarding the possible role of IL1B -511 C/T polymorphism in AITD. The TT genotype has been described as a protective variant for GD [12], [53], [54], however, other studies did not report any association between this polymorphism and GD or HT [10], [55], [56]. In the present study, we also did not observe a significant association between the IL1B -511 C/T polymorphism and GD or HT.…”
Section: Discussioncontrasting
confidence: 88%
“…Several studies have reported conflicting results regarding the possible role of IL1B -511 C/T polymorphism in AITD. The TT genotype has been described as a protective variant for GD [12], [53], [54], however, other studies did not report any association between this polymorphism and GD or HT [10], [55], [56]. In the present study, we also did not observe a significant association between the IL1B -511 C/T polymorphism and GD or HT.…”
Section: Discussioncontrasting
confidence: 88%
“…IL-1␣ and IL-1␤ are located at the same chromosome band (2q14) as CTLA-4; indeed, associations of these two genes with GD have been described in many studies. A family-based study and a case-control study showed a significant association of IL-1␣ (rs1800587, T-889 C) with GD, whereas Hunt et al failed to do so [15,18,27]. Polymorphism in IL-1␤ (rs16944, A-511 G) has reported their possible role in GD in Asian population, but not with GO.…”
Section: Discussionmentioning
confidence: 88%
“…Several genetic association studies provided suggestive evidence of linkage of GD to the polymorphisms of IL-1␣ and IL-1␤ genes. Two single-nucleotide polymorphisms (SNPs) included in other studies, one located in the 5= flanking region at position Ϫ889 (rs1800587, T-889 C) in the IL-1␣, and the other in the 5= flanking region at position Ϫ511 (rs16944, A-511 G) in the IL-1␤ gene, have been found associated with the risk for GD and GO, but these results are still inconclusive [15][16][17][18].…”
Section: Introductionmentioning
confidence: 96%
“…20 We have also shown significant associations between GO and IL-1a and IL-1RA gene polymorphisms in Iranian patients. 24 This study revealed significant associations between GO and certain polymorphisms in INF-g, TNF-a, and IL-12 genes.…”
Section: Discussionmentioning
confidence: 99%